Immigration, ethnic fractionalization, and the fiscal burden in the OECD - Federico Guerrero; Elliott Parker (European Journal of Government and Economics (EJGE), 2022)
This study considers the impact of immigration and ethnic diversity on government spending in 31 OECD countries over 25 years and compares the marginal effects for expenditures and revenues to approximate the fiscal burden. Results suggest that ethnic fractionalization, not immigration itself, has a negative impact on spending in the OECD. On the whole, immigrants tend to contribute more in taxes than they cause in expenditures, at least relative to the averages for the population as a whole, but this effect is reversed for immigrants from poorer countries.
Keywords: F22; H41; P50; 330; immigration; ethnic diversity; fractionalization; government revenues; government expenditures